Synthesis and Characterization of Monodisperse Hydrous Colloidal Zirconia Nanoparticles - Nguyen, Thi Dieu Linh; Nguyen, Quang Tung; Do, Quang Tham; Nguyen, Vu Giang; Tran, Huu Trung; Le, Thi My Hanh; Nguyen, Thi Thu Trang; Nguyen, Thuy Chinh; Thai, Hoang; Tran, Thi Mai; Do, Van Sy (Communications in Physics, 2020)
The suspension of hydrous colloidal zirconia particles (CZPs) was prepared from zirconium oxychloride solutions via thermal hydrolysis at acidic condition and at boiling point of 110 ºC for 72 h. Characterization of the obtained suspension and dried solid ZrO2 was performed by DLS, FESEM, FTIR, XRD and TGA measurements. Purification via dialysis membrane can maintain the monodispersion of the colloidal suspension when stabilized at pH6. The suspension contained almost sheet-like colloidal particles with amorphous structure with size ranges from 70 to 140 nm in wide and about 40-60 nm in thickness. The formula of hydrous CZPs can be expressed as ZrO2.2H2O.